ENERGY AND COST SAVING OF AIR CONDITIONING SYSTEM USING MAGNETIC BEARING CHILLER FOR HOTEL A IN JAKARTA - Agus Marjianto; Hafthirman Hafthirman; Prihadi Setyo Darmanto (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
The use of magnetic bearing chillers in hotel air conditioning systems is an opportunity for energy or cost savings. This study will compare the electrical energy consumption and cost analysis of the centralized air conditioning system using magnetic bearing chiller that uses variable flow to another air conditioning system such as the centralized air conditioning using constant flow chiller and the VRF split air conditioning system at Hotel A in Jakarta. The calculation of energy consumption for each air conditioning system is carried out for a year. Meanwhile, the cost analysis will be carried out using the life cycle cost method for 20 years. The air conditioning system which has the least energy consumption and has the lowest life cycle cost is the best air conditioning system for this hotel building. The maximum cooling load that occurs in Hotel A is 3,281 kW. From the results of energy calculations and cost analysis, a centralized air conditioning system with magnetic bearing chiller with variable flow is the best choice to Hotel A or similar building to Hotel A, with IKE (Intensitas Konsumsi Energi) value of 84 kWh/(m2.year), and a total cost of 78,873,678,478.00 IDR for a period of 20 years.